Automatic Adjustment of Keyboard Settings Can Enhance Typing. - Koester, Heidi Horstmann; Mankowski, Jennifer (Assistive Technology)
We developed and evaluated a software tool for the automatic configuration of Windows keyboard settings. The software is intended to accommodate the needs of people with physical impairments, with a goal of improved productivity and comfort during typing. The prototype software, called AutoIDA, monitors user activity during performance of regular computer tasks and recommends the Sticky Keys and key repeat settings to meet the user’s specific needs. The evaluation study included fourteen individuals with upper extremity impairments. AutoIDA recommended changes to the default keyboard settings for 10 of the 14 participants. For these individuals, average typing speed was essentially the same whether users typed with the default keyboard settings (5.5 wpm) or the AutoIDA-recommended settings (5.3 wpm). Average typing errors decreased with use of the recommended settings, from 17.6% to 13.3%, but this was not quite statistically significant (p = .10). On an individual basis, four participants appeared to improve their overall typing performance with AutoIDA-recommended settings. For more specific metrics, AutoIDA prevented about 90% of inadvertent key repeats (with a revised algorithm) and increased the efficiency and accuracy of entering modified (shifted) characters. Participants agreed that software like AutoIDA would be useful to them (average rating 4.1, where 5 = strongly agree).